2022
DOI: 10.3390/ijerph19095197
|View full text |Cite
|
Sign up to set email alerts
|

Social Media User Behavior and Emotions during Crisis Events

Abstract: The wide availability of smart mobile devices and Web 2.0 services has allowed people to easily access news, spread information, and express their opinions and emotions using various social media platforms. However, because of the ease of joining these sites, people also use them to spread rumors and vent their emotions, with the social platforms often playing a facilitation role. This paper collected more than 190,000 messages published on the Chinese Sina-Weibo platform to examine social media user behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Whatever model practitioners find most useful, this study has demonstrated that social media has raised the stakes for crisis management. Organizations cannot afford to ignore the information flowing freely and urgently into the social realms, especially during the response stage (Gu et al, 2022). Without proper planning, social media will be ignored during the response stage as the organization is overwhelmed by the crisis.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Whatever model practitioners find most useful, this study has demonstrated that social media has raised the stakes for crisis management. Organizations cannot afford to ignore the information flowing freely and urgently into the social realms, especially during the response stage (Gu et al, 2022). Without proper planning, social media will be ignored during the response stage as the organization is overwhelmed by the crisis.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…EMAs could gather first-hand information related to an emergency from social media, including people's emotions, messages of support, and political content, which can more intuitively display experiences, views, and opinions to directly inform emergency rescue operations [24]. After the breakout of COVID-19 in Wuhan, content and sentiment analyses were applied to Chinese microblogging UGCs to understand people's behaviors and emotions in response to the death of Dr. Wenliang Li [25]. Pradeepa et al [26] believed that EMAs could monitor the public's attitudes towards emergencies and take actions quickly by collecting and analyzing social media UGCs.…”
Section: Related Work 21 Utilization Of Social Media In Emergenciesmentioning
confidence: 99%
“…Next, social isolation may occur due to lockdowns, with the loss of face-to-face interaction resulting in negative emotions ( Qiu et al, 2020 ). As individuals can choose to be fully or partially anonymous on social media, they may view these platforms as safe places to freely express their negative emotions during the pandemic ( Gu et al, 2022 ). Moreover, for individuals who perceive their offline realities as unfulfilling due to social restrictions, social media can serve as an alternative avenue for them to both maintain existing social bonds and form new ones ( O’Day and Heimberg, 2021 ).…”
Section: Introductionmentioning
confidence: 99%